Early Risks of Death, Stroke/Systemic Embolism, and Major Bleeding in Patients With Newly Diagnosed Atrial Fibrillation: Results From the GARFIELD-AF Registry. Issue 6 (5th February 2019) - Bassand, Jean-Pierre; Virdone, Saverio; Goldhaber, Samuel Z.; Camm, A. John; Fitzmaurice, David A.; Fox, Keith A.A.; Goto, Shinya; Haas, Sylvia; Hacke, Werner; Kayani, Gloria; Mantovani, Lorenzo G.; Misselwitz, Frank; et al.
Abstract : Background: Atrial fibrillation is associated with increased risks of death, stroke/systemic embolism, and bleeding (incurred by antithrombotic therapy), which may occur early after diagnosis. Methods: We assessed the risk of early events (death, stroke/systemic embolism, and major bleeding) over 12 months and their relation to the time after diagnosis of atrial fibrillation in 52 014 patients prospectively enrolled in the GARFIELD-AF registry (Global Anticoagulant Registry in the FIELD–Atrial Fibrillation) between March 2010 and August 2016. Results: Over 12 months, 2140 patients died (mortality rate, 4.3; 95% CI, 4.2–4.5 per 100 person-years), of whom 288 (13.5%) died in the first month (6.8; 95% CI, 6.1–7.6). Over 12 months, 657 patients had a stroke/systemic embolism (1.3; 95% CI, 1.2–1.4) and 411 had a major bleeding (0.8; 95% CI, 0.8–0.9). During the first month, the rates (per 100 person-years) of stroke/systemic embolism and major bleed were 2.3 (95% CI, 1.9–2.8) and 1.5 (95% CI, 1.2–1.9), respectively. The elevated 1-month mortality rate was mostly attributable to cardiovascular mortality (3.5; 95% CI, 3.0–4.1), in particular, heart failure, sudden death, and acute coronary syndromes (1.0 [95% CI, 0.8–1.4], 0.6 [95% CI, 0.4–0.8], and 0.5 [95% CI, 0.3–0.8], respectively). Age, heart failure, prior stroke, history of cirrhosis, vascular disease, moderate-to-severe kidney disease, diabetes mellitus, and living in North or Latin America were independent predictors of a higher risk of early death, whereas anticoagulation and living in Europe or Asia were independent predictors of a lower risk of early death. A predictive model developed for the 1-month risk of death had a C-statistic of 0.81 (95% CI, 0.78–0.83). Conclusions: The increased hazard of early events, in particular, cardiovascular mortality, in newly diagnosed atrial fibrillation points to the importance of comprehensive care for such patients and should alert clinicians to detect warning signs of possible early mortality. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01090362. Abstract : Supplemental Digital Content is available in the text.